(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Original documents designed to meet the communicative function of French speakers are important in language lessons, since their use is suitable for teaching that is more realistic and oriented to current events, more sensitive to motivations. This article will help you learn a foreign language and identify its features.